1999
DOI: 10.1111/j.1558-5646.1999.tb05336.x
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative and Molecular Genetic Architecture of a Subdivided Species

Abstract: In an effort to elucidate the evolutionary mechanisms that determine the genetic architecture of a species, we have analyzed 17 populations of the microcrustacean Daphnia pulex for levels of genetic variation at the level of life-history characters and molecular markers in the nuclear and mitochondrial genomes. This species is highly subdivided, with approximately 30% of the variation for nuclear molecular markers and 50% of the variation for mitochondrial markers being distributed among populations. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
158
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(177 citation statements)
references
References 30 publications
14
158
0
5
Order By: Relevance
“…Comparison of F st values for molecular markers and quantitative traits Some authors have raised concerns about the effects of epistasis and dominance on the expected value of Q st (Lynch et al, 1999). In the case of epistasis, Whitlock (1999) has shown that additive-by-additive epistasis would decrease the expectation of Q st .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of F st values for molecular markers and quantitative traits Some authors have raised concerns about the effects of epistasis and dominance on the expected value of Q st (Lynch et al, 1999). In the case of epistasis, Whitlock (1999) has shown that additive-by-additive epistasis would decrease the expectation of Q st .…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of variation of quantitative traits is likely to be driven by environmental factors such as natural selection pressures (Lynch et al, 1999;Petit et al, 2000), whereas most molecular markers are considered effectively neutral. The combination of quantitative and molecular measures of variation allows one to test empirically hypotheses relating to different modes of phenotypic evolution in subdivided populations.…”
Section: Introductionmentioning
confidence: 99%
“…The neutral model provides a benchmark against which actual data on trait divergence can be compared. A number of methods of this kind have been proposed for the univariate (singletrait) case (Lande 1977;Charlesworth 1984;Turelli et al 1988;Lynch 1990;Lynch et al 1999;Estes and Arnold 2007). These approaches assess the statistical significance of departures from neutral rates of evolution.…”
mentioning
confidence: 99%